Chemoradiotherapy for locally advanced pancreatic cancer patients: is it still an open question? - Sawicka, Emilia; Mirończuk, Anna; Wojtukiewicz, Marek Z.; Sierko, Ewa (Contemporary Oncology/Współczesna Onkologia, 2016)
Operable pancreatic cancer is characterized by a high risk of recurrence. Efforts are made to incorporate new therapies. Throughout the world there is a lack of uniform recommendations concerning the adjuvant treatment of pancreatic cancer patients, due to confusing evidence-based data. The patients recruited to clinical trials differ from the population of patients treated in everyday practice. These differences have an influence on tolerance of treatment, toxicity and results of therapy. The decision on administration of adjuvant treatment is made individually and differs from center to center. A review of the literature concerning both results and tolerance of postoperative chemoradiotherapy of pancreatic cancer patients is presented.